Aberration-corrected electron microscopy of nanoparticles - Yacamán, Miguel José; Santiago, Ulises; Mejía Rosales, Sergio (Springer International Publishing, 2015)
The early history of scanning transmission electron microscopy (STEM) is reviewed as a way to frame the technical issues that make aberration correction an essential upgrade for the study of nanoparticles using STEM. The principles of aberration correction are explained, and the use of aberration-corrected microscopy in the study of nanostructures is exemplified in order to remark the features and challenges in the use of this measuring technique